Learning Public Speaking Skills from an Ethnography Study of `Kampung Inggris` - Estiana Tri Karmala; Diah Kristina; Slamet Supriyadi (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
Learners who have studied the English language for several years are still not able to speak English fluently and they can solve the weakness of English teaching at school or university and the need of society to learn English by English course. ―Daffodils‖ English course in Kampung Inggris is acknowledged as an alternative solution for English learners. The objectives of the research are: (1) to investigate why ―Daffodils‖ English course in Kampung Inggris as an alternative solution for English learners (2) to explore the effects of Public Speaking at ―Daffodils‖ English course in Kampung Inggris. This is an ethnography study research. The ethnography study data are collected through document analysis, via in-depth interview (students and teacher), and observation public speaking class. The research findings show that; (1) ―Daffodils‖ English course solves the weakness of English teaching to learn English, (2) the effects of Public Speaking at ―Daffodils‖ English course can develop students’ pronunciation, vocabulary, grammatical understanding and language experience and give good contribution for English learners. In conclusion, it can be concluded that public speaking at ―Daffodils‖ English course in Kampung Inggris gives solution for English learners to learn.